Current Cadastral Trends-A Literature Review of the Last Decade - Usak, Burak; Cagdas, Volkan; Kara, Abdullah (MDPI, 2024)
Today, population growth, high urbanization rates, and global agenda issues have led to the intensive use of land and air and water spaces, and cadastral systems that manage the people-land relationship have evolved into a multi-purpose form that supports various land-based activities. This situation has necessitated the modernization of traditional land administration and cadastral systems to manage the people-land relationship effectively. This study conducts a literature review on current cadastral trends emerging from the perspective of modern land administration systems (LASs). A total of 367 studies published in the Web of Science (WoS) database in the last decade on 3D cadastre, technical infrastructure cadastre, maritime cadastre, public law restriction (PLR) cadastre, fit-for-purpose land management, and disaster-sensitive cadastral trends are analyzed. The study aims to analyze the interest of the land administration community in current cadastral trends and present the results. The analysis results show that the most researched trend is 3D cadastre, and the least researched trends are PLRs cadastre and disaster-responsive cadastre. LADM stands out as a widely used framework across the studies.
Keywords: 3D cadastre; cadastre; disaster responsive cadastre; FFPLA; land administration; LADM; modern land administration system; marine cadastre; PLRs cadastre; technical infrastructure cadastre; SPATIAL DATA INFRASTRUCTURE; UNDERGROUND SPACE; DATA-COLLECTION; BUILDING MODEL; LAND; URBAN; INFORMATION; LEGAL; MANAGEMENT; Environmental Sciences & Ecology